Formulation of the problem and special features of interaction of longitudinal and lateral movement of aircraft - Кудиненко, А. В. (Proceedings of National Aviation University (archive), 1998)
Considered are the formulation and special features of the problems of interaction of longitudinal and lateral movements of flying vehicles. Described here is the synchronization of the movements. We suggest that the generalization of the principle of division of the motions be used for the analysis of critical flight conditions at critical angle of attack